2017
DOI: 10.1002/jsfa.8388
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the binding capacity of mercurial species in Lactobacillus strains

Abstract: BACKGROUND Metal sequestration by bacteria has been proposed as a strategy to counteract metal contamination in foodstuffs. Lactobacilli can interact with metals, although studies with important foodborne metals such as inorganic [Hg(II)] or organic (CH3Hg) mercury are lacking. Lactobacilli were evaluated for their potential to bind these contaminants and the nature of the interaction was assessed by the use of metal competitors, chemical and enzymatical treatments, and mutants affected in the cell wall struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 37 publications
0
19
0
3
Order By: Relevance
“…It has been postulated that binding of heavy metals by lactic acid bacteria occurs mainly via surface interactions with cell wall components and that low proportions of the toxic are internalized through processes that may involve specific/unspecific transport or diffusion (for review, see: Mrvcic et al, 2012 ; Zoghi et al, 2014 ; Chiocchetti et al, 2018 ). This notion has been specifically proven for L. casei BL23 ( Alcantara et al, 2017 ). Since most poly-P is accumulated intracellularly as cytoplasmic granules, it would therefore have a low interaction with mercury.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…It has been postulated that binding of heavy metals by lactic acid bacteria occurs mainly via surface interactions with cell wall components and that low proportions of the toxic are internalized through processes that may involve specific/unspecific transport or diffusion (for review, see: Mrvcic et al, 2012 ; Zoghi et al, 2014 ; Chiocchetti et al, 2018 ). This notion has been specifically proven for L. casei BL23 ( Alcantara et al, 2017 ). Since most poly-P is accumulated intracellularly as cytoplasmic granules, it would therefore have a low interaction with mercury.…”
Section: Discussionmentioning
confidence: 79%
“…Our observations indicate that the poly-P-influenced mechanisms that affect mercury resistance would not necessarily ave an impact on the capacity to accumulate mercury. It has been recently shown that lactobacilli can efficiently sequester Hg(II) as well as CH 3 Hg, the main mercurial form found as food contaminant ( Alcantara et al, 2017 ; Jadan-Piedra et al, 2017 ). However, our results question the role of poly-P in the mercury retention mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Binding of both forms was immediate and mainly occurred at the cell wall. Cell viability was not required for binding; in fact, an increase of binding capacity was observed for heat-killed cells (Alcántara et al, 2017). Furthermore, Lactobacillus casei mutants affected in genes involved in the modulation of the negative charge of the cell wall anionic polymer lipoteichoic acid showed increased Hg biosorption.…”
Section: Metals and Metalloidsmentioning
confidence: 98%
“…Another study investigated the binding capacity of inorganic Hg [Hg(II)] and the organic form methylmercury (CH3Hg) to various strains of Lactobacillus (Alcántara et al, 2017).…”
Section: Metals and Metalloidsmentioning
confidence: 99%
“…Several studies have revealed that specific Lactobacillus strains alleviated heavy metal toxicity (Tian et al, 2015 ; Trinder et al, 2016 ; Yu et al, 2016 ; Alcantara et al, 2017 ). Recently, Majlesi M et al have proved the L. plantarum and Bacillus coagulans protected significantly against mercury toxicity in liver and kidney in rats by decreasing the mercury, creatinine, urea, bilirubin, ALT, and AST level, and preventing alterations in the levels of GPx and SOD (Majlesi et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%